Development and Validation of a Questionnaire for the Assessment of Diabetic Peripheral Neuropathy: Implications for Clinical Practice in Physical Therapy and Patient Management - Constantin CIUCUREL; Mariana TUDOR; Elena Ioana ICONARU (Romanian Journal of Physical Therapy)
Introduction: The aim of this study is to develop and validate a questionnaire that evaluates the impact of diabetic peripheral neuropathy (DPN) on quality of life and functional capacity in older adults, while also exploring correlations between clinical factors and DPN severity to guide personalized treatment strategies. Methods and materials: A systematic literature review identified key symptoms of DPN, leading to the development of the 20-item Questionnaire for the Assessment of the Impact of Diabetic Peripheral Neuropathy (QAIDPN). The QAIDPN evaluates neuropathic pain, sensory changes, balance difficulties, functional limitations, and overall quality of life using a Likert scale (0-4). It was piloted with 56 DPN patients (mean age 72.45 ± 5.72 years) to assess internal consistency. Correlational analyses examined relationships between questionnaire outcomes and age, sex, diabetes duration, and highest recorded blood glucose level (HRBGL). Results: The QAIDPN demonstrated high internal consistency (Cronbach's alpha = 0.93), indicating excellent agreement among the items. QAIDPN scores significantly correlated with HRBGL (r = 0.80, p ≤ 0.001), diabetes duration (r = 0.64, p ≤ 0.001), and age (r = 0.56, p ≤ 0.001). Discussion: This study developed and validated the QAIDPN, a novel tool for assessing DPN's effects in older adults. Covering a wide range of domains, it provides valuable insights into DPN’s impact on quality of life and functional capacity. QAIDPN is a reliable method for evaluating DPN, aiding in the development of therapeutic algorithms to improve patient outcomes. Our correlational analysis identified significant associations between QAIDPN scores and clinical outcomes such as HRBGL, diabetes duration, and age (p ≤ 0.001), guiding targeted treatment strategies for DPN. Conclusions: The development and validation of the QAIDPN enhance clinical research and practice by providing a reliable method for evaluating DPN and serving as a foundation for creating targeted physical therapy algorithms aimed at improving patient outcomes.